Shaddock peel-derived N-doped carbon quantum dots coupled with ultrathin BiOBr square nanosheets with boosted visible light response for high-efficiency photodegradation of RhB. (15th May 2023) - Qi, Yu; Zhao, Jinjiang; Wang, Hongtao; Zhang, Aiming; Li, Jinping; Yan, Meifang; Guo, Tianyu
Abstract: In the present work, we constructed a serials of novel shaddock peel-derived N-doped carbon quantum dots (NCQDs) coupled with BiOBr composites. The result showed that the as-synthesized BiOBr (BOB) was composed of ultrathin square nanosheets and flower-like structure, and NCQDs were uniformly dispersed on the surface of BiOBr. Furthermore, the BOB@NCQDs-5 with optimal NCQDs content displayed the top-flight photodegradation efficiency with ca. 99% of removal rate within 20 min under visible light and possessed excellent recyclability and photostability after 5 cycles. The reason was attributed to relatively large BET surface area, the narrow energy gap, inhibited recombination of charge carriers and excellent photoelectrochemical performances. Meanwhile, the improved photodegradation mechanism and possible reaction pathways were also elucidated in detail. On this basis, the study opens a novel perspective to obtain a highly efficient photocatalyst for practical environment remediation. Graphical abstract: Image 1 Highlights: Shaddock peel-derived N-doped carbon quantum dots were successfully achieved. The incorporation of NCQDs reduced the band gap and enhanced visible light adsorption. The optimum BOB@NCQDs-5 photocatalyst can photodegrade RhB of ca. 99% within 20 min. The possible photodegradation route of RhB was proposed.